Home Delivery Meal Kits Online Food Safety-Related Information: A Perspective - Maneerat, Nitjaree; Byrd, Karen; Almanza, Barbara; Behnke, Carl; Nelson, Douglas (My University, 2024)
The recent popularity of home delivery meal kits (HMK) has prompted concerns about its integrity and safety. On the basis of a food safety-related information evaluation of the common US-based HMK vendors’ websites, this perspective highlights opportunities for improvement with the adequacy and accessibility of relevant information on HMK websites, an important resource for communicating food safety best practices to consumers. Identified gaps in information and inadequate delivery protocols potentially increase the risk of offering unsafe food to consumers. Suggestions for future research and recommendations for vendors, policymakers, and regulators to help protect consumers from potential foodborne illness risks are also discussed.
Keywords: delivery protocol; food safety; home delivery meal kits; meal kits websites; online information